A new ultrasonic vibration machine for honing. (1st October 2007) - Zhu, X.J.; Gao, Y.X.; Xu, H.J.
The ultrasonic vibration machine for honing is a new high-tech product that combined technologies with machine, electricity and sound. It can be widely used in motor vehicle industry to improve the surface quality of engine cylinder sleeve. In this paper, the constitution and the structure of this device are described in detail; the key technology such as supersonic generator, transducer and amplitude pole are introduced, involving their design and application; and the experimental result is finally given.